The interpersonal theory of suicide risk in male US service members/veterans: the independent effects of perceived burdensomeness and thwarted belongingness - Rebecca K. Blais; Kevin J. Grimm (European Journal of Psychotraumatology)
Introduction: Suicide rates remain high among US military service member/veteran (SM/V) males with overall trends showing an upward trajectory. Several empirical studies and official US government reports show that interpersonal challenges can substantially increase suicide risk. One theory, the Interpersonal Theory of Suicide (IPT), focuses thwarted belongingness, perceived burdensomeness, capability for suicide, and their interactions, as key contributors to suicide risk. Extant military studies are subscribed to specific subsamples and/or do not test the full theory. This has resulted in mixed findings or findings with limited generalizability. The current study addressed these limitations.Method: A convenience sample of 508 male SM/Vs completed self-report measures of lifetime suicide ideation, likelihood of making a future attempt, thwarted belongingness, perceived burdensomeness, capability for suicide, and demographics. Suicide ideation and risk was regressed on IPT variables, relevant interactions, and covariates.Results: The variance accounted for in suicide ideation and likelihood of a future attempt was 32% and 62%, respectively. Higher perceived burdensomeness was associated with suicide ideation, and higher thwarted belongingness had a marginally significant association with suicide ideation. The presence of suicide ideation and higher thwarted belongingness were associated with the likelihood of making a future attempt. Capability for suicide was not associated with the likelihood of making a future attempt.Discussion: Perceived burdensomeness, suicide ideation, and thwarted belongingness appear to individually create risk for future suicide behaviour among US military service members and veterans. Additional work is needed to establish comprehensive theories of suicide risk in this population.